ALGLUCOSIDASE ALFA - A NEW STAGE IN THE THERAPY OF INFANTILE POMPE DISEASE - E. N. Basargina; E. N. Arkhipova; V. S. Ermolenko (Union of pediatricians of Russia, 2014)
Pompe disease is a rare severe hereditary disease caused by excessive glycogen storage in organs and target tissues due to the acid α-glucosidase gene mutation. Infantile and adult Pompe disease is characterized by involvement of cardiovascular, respiratory and muscular systems in the pathological process. The only specific method of treating Pompe disease is enzyme replacement therapy (intravenous administration of recombinant human acid glucosidase), the effectiveness whereof depends on the time the therapy started. Since such a therapy was introduced into practice, Pompe disease mortality decreased by 79%. 6 children with infantile Pompe disease were observed and treated at the cardiovascular care unit of the Scientific Center of Children's Health in 2011‑2014. The article presents a clinical case demonstrating capabilities of diagnosing infantile Pompe disease in Russia and effective application of alglucosidase alfa in 4-month-old child.